Mitigating Digital Brain Fatigue Through Structured Reflection: A Self-Regulated Learning Intervention in Science Teacher Education - Sri Masnita Pardosi; Retno Dwi Suyanti; Nadia Mubarokah; Alvi Sahrin Nasution; Suci Indah Putri (Jurnal Pendidikan Sains Indonesia, 2026)
The increasing digitization of science education has intensified concerns about digital brain fatigue among pre service science teachers, a state of cognitive depletion characterized by reduced attentional control and learning efficiency. While reflective journaling supports metacognitive development, its potential as a structured intervention for cognitive regulation remains underexplored. This quasi experimental study investigated the effectiveness of a structured reflective daily journal intervention grounded in self regulated learning principles in reducing digital brain fatigue. Participants were 52 Indonesian pre service science teachers engaged in digitally intensive science learning. They completed a four week intervention comprising seven Likert scale items targeting forethought, performance control, and self reflection phases of self regulated learning. Digital brain fatigue was measured using a validated 15-item scale assessing attentional depletion, cognitive exhaustion, and reduced learning efficiency. Results revealed a significant decrease in digital brain fatigue from pretest (M = 3.87, SD = 0.54) to posttest (M = 3.21, SD = 0.49), with a mean difference of 0.66 (t = 7.84, p < 0.001). Thematic analysis of reflective journals revealed that physical indicators (eye strain: 94.4%; headaches: 86.1%) and behavioral indicators (unnecessary social media checking: 97.2%) were reported more frequently than purely cognitive indicators. Structured reflective daily journals effectively mitigate digital brain fatigue by enhancing metacognitive awareness, facilitating cognitive load management, and strengthening behavioral regulation. These findings extend theoretical frameworks linking self regulated learning to cognitive well being and offer a practical strategy for promoting cognitive sustainability in higher education